2021
DOI: 10.3390/molecules27010211
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of MicroRNAs in Bone Diseases and Their Therapeutic Potential

Abstract: MicroRNAs (miRNAs) are a class of small (20–24 nucleotides), highly conserved, non-coding RNA molecules whose main function is the post-transcriptional regulation of gene expression through sequence-specific manners, such as mRNA degradation or translational repression. Since these key regulatory molecules are implicated in several biological processes, their altered expression affects the preservation of cellular homeostasis and leads to the development of a wide range of pathologies. Over the last few years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 175 publications
(215 reference statements)
0
20
0
Order By: Relevance
“…A recent study has shown that endogenous circRNAs act as miRNA sponges to attenuate the function of miRNAs ( 53 ). A study has also confirmed that the decrease in osteogenic potential in chronic inflammatory environments is associated with miRNA dysregulation ( 54 ). In the current study, vast miRNAs, especially miR-182, miR-1200, miR-338, miR-576, miR-623, were identified as possibly interacting with hsa_circ_0099630 based on a bioinformatics analysis.…”
Section: Discussionmentioning
confidence: 87%
“…A recent study has shown that endogenous circRNAs act as miRNA sponges to attenuate the function of miRNAs ( 53 ). A study has also confirmed that the decrease in osteogenic potential in chronic inflammatory environments is associated with miRNA dysregulation ( 54 ). In the current study, vast miRNAs, especially miR-182, miR-1200, miR-338, miR-576, miR-623, were identified as possibly interacting with hsa_circ_0099630 based on a bioinformatics analysis.…”
Section: Discussionmentioning
confidence: 87%
“…More specific biomarkers of the diseases (microRNAs, extracellular vesicles) could be studied in order to find specific patterns in osteomalacia [ 74 ].…”
Section: Research Gaps and Potential Development In The Fieldmentioning
confidence: 99%
“…Among the biomolecules transported by EVs, noncoding RNAs including lncRNAs and miRNAs exhibit various roles in metastatic bone disease [151,152]. Recent studies demonstrated that several miRNAs are involved in the regulation of osteoclasts and osteoblasts during bone metastasis progression in breast, prostate and colorectal cancer [153][154][155][156][157][158][159][160][161].…”
Section: Secreted Molecules and Extracellular Vesicles In Bone Metast...mentioning
confidence: 99%